Assessing the impact of development institutions in the Russian Far East - Georgiy A. Borshchevskiy (Управленец)
Despite the fact that development institutions are quite widespread, management practice lacks generally accepted methods for their assessment. The article aims to compare the performance of several acting and reorganized institutions to ascertain whether their reconfiguration is optimal. Methodologically, the study rests on Schumpeterian growth theory, structural change theory, and new institutionalism. The indicators characterizing the performance of the development institutions in the Russian Far East were obtained from the Unified Interdepartmental Information and Statistical System for 2000–2022. The data sets were transformed using the principal component analysis; the difference-in-differences method was applied to assess the outcome produced by the development institutions. Out of five development institutions under review, three of them revealed a statistically significant negative impact on the dynamics of relevant indicators of the Far Eastern Federal District, while two of them showed an insignificant effect. Granting development institutions a clear legal status will allow integrating them into the unified system of public authority of the Russian Federation and shaping a policy on their formation, functioning and performance evaluation with national priorities taken into account. A development institution is perceived as a macroeconomic agent since its activities are not aimed at implementing a specific project, but at the socio-economic development of a region or an industry. Hence, it is reasonable to assess them using macroeconomic indices. Institutions exerting no significant effect on the development of the territory (industry) over several years are subject to reorganization.